Features and hospital outcomes of coronary artery bypass grafting in patients with calcification of target coronary arteries - R. S. Akchurin; A. A. Shiryaev; V. P. Vasiliev; D. M. Galyautdinov; E. E. Vlasova; I. S. Fedotenkov; S. K. Kurbanov; G. B. Mayorov (Российский кардиологический журнал, 2020)
Aim. To compare strategy and early results of coronary artery bypass grafting (CABG) in patients with and without calcification of target coronary arteries (TCA).Material and methods. The prospective study analyzed the data of patients (n=462) who underwent elective isolated CABG in 2017-2018 using cardiopulmonary bypass and microsurgery. Two groups were distinguished: group 1 — patients with TCA calcification (n=108), group 2 — patients without TCA calcification (n=354). In cases where the distal coronary artery lesion did not allow standard bypass grafting, additional complex anastomoses were provided. A comparison of intraoperative parameters and early results of CABG was carried out.Results. In groups 1 and 2, the revascularization index did not differ significantly and was 4,5 and 4,3, respectively. The frequency of complex surgical interventions in group 1 was higher: for example, ‘Y’ grafts were used in groups 1 and 2, respectively, in 32% (35/108) and 12% (44/354), p<0,05; sequential anastomoses in 14% (15/108) and 7% (26/354), p<0,05; prolonged patch-angioplasty — in 21% (23/108) and 5% (16/354), p<0,05; anastomoses with arteries <1,5 mm in diameter — in 33% (36/108) and 4% (14/354), p<0,05; coronary endarterectomy in 17% (18/108) and 5% (16/354), p<0,05, respectively. The duration of cardiopulmonary bypass was longer in group 1. At the same time, the hospital clinical results did not differ significantly: mortality was not registered; the frequency of perioperative myocardial infarction was 1,8% (group 1) and 1,1% (group 2); the need for inotropes, frequency of arrhythmia, length of stay in the intensive care unit and hospital were similar; there were no cases of in-hospital angina recurrence.Conclusion. CABG in patients with calcification of TCA is associated with surgical challenges and need for complex adjunct techniques. Nevertheless, complete surgical revascularization is real in these cases, and the hospital results are comparable to those in patients without calcification.